PERSPEKTIF ISLAM TERHADAP ILMU PENGETAHUAN - Duriana Duriana (DIALEKTIKA, 2018)
This paper is a research on the Islamic perspective on Science. The purpose of this study was to determine how the Islamic perspective on science in order to answer the challenges of the times. The main issues are the focus of this study is: How can the Islamic perspective on science? This study is a research library with a theological approach. This approach is used to weigh the charge of Islamic religious teachings derived from the Qur'an and Sunnah, for the sake of the mission of Islam as well as to distinguish religious studies with other studies. Based on the results of the study found that Islam places great emphasis on studying and uplift those who have knowledge. Islam emphasizes to find useful knowledge does not distinguish between theology and general science (non-religion / world)